Autoimmune lymphoproliferative syndrome in pregnancy: A case of favorable mother–fetal outcome in a well‐controlled disease. Issue 3 (10th October 2014) - Patti, Simona; Perrone, Giuseppina; De Pratti, Valentina; Quinti, Isabella; Milito, Cinzia; Brunelli, Roberto
Abstract The autoimmune lymphoproliferative syndrome (ALPS) is a disorder of abnormal lymphocyte survival caused by the dysregulation of the Fas apoptotic pathway. The Fas gene is expressed at the maternal–fetal interface and is involved in the regulation of immune response and implantation. Altered Fas expression may result in altered apoptosis and, ultimately, affect both the immune response and implantation; it is in fact associated with recurrent pregnancy loss, preterm premature rupture of membranes and pre‐eclampsia. Currently, there are over 500 cases of ALPS reported worldwide from various racial and ethnic backgrounds. Up to date, the published work contains no specific reports on pregnancy outcome in women affected by ALPS. We present a case of full‐term uneventful pregnancy in a patient affected by ALPS. A specific clinical follow‐up in a pregnant woman with primary immunologic disease is suggested.